EFEKTIVITAS PROGRAM POSYANDU LANSIA (Studi : Posyandu “Sehat Ceria” Kelurahan Medokan Semampir Kecamatan Sukolilo Kota Surabaya) - Fiqri Putra Bafelanna; Sri Wahyuni (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2021)
Posyandu Elderly is a service for the elderly that focuses on promotive and preventive services without neglecting curative and rehabilitative efforts. The activities at the 1998 Elderly Posyandu are a forum for services to the elderly in the community which focuses on health, psychological, and spiritual services, fulfilling nutrition so that the elderly can meet their needs and adequate social welfare. The purpose of this study was to determine the effectiveness of the "Healthy Cheerful" Elderly Posyandu Program, Medokan Semampir Village, Sukolilo District, Surabaya City. The data collection of this research used a qualitative method to determine the effectiveness of the "Healthy Cheerful" Elderly Posyandu Program, Medokan Semampir Village, Sukolilo District, Surabaya City. The implementation of this program is carried out with promotive, preventive, curative and rehabilitative programs. This study uses Budiani's theory of effectiveness which consists of variables of program accuracy, program socialization, program objectives and program monitoring. Various policies and programs implemented by the government, among others, are contained in Government Regulation Number 43 of 2004 concerning the Implementation of Efforts to Improve the Welfare of the Elderly. The elderly posyandu program is preventive as a preventive effort, curative as an effort to treat the elderly, rehabilitative as an effort to recover and promote as a form of introduction to the program for the elderly. Indicators of program socialization and program monitoring have been running well and effectively. The results of the research obtained are the Mayor of Surabaya Regional Regulation Number 3 of 2014 concerning the implementation of efforts to improve the welfare of the elderly has been effective, while the less effective variables are the accuracy of the program and program objectives.